HUBUNGAN INDEKS MASSA TUBUH DENGAN KADARKOLESTEROL TOTAL PADA LANSIA DI POSYANDU LANSIA "NGUDIWARAS" DESA BLULUKAN KECAMATAN COLOMADU,KARANGANYAR, JAWA TENGAH - YULIANA, EMA, Siti Zulaekah, A., M.Si, Dwi Sarbini, SST., M.Kes (2016)
Introduction : The nutritional status of elderly can be simply monitored by using the body mass index, particularly the nutritional status correspond with the overweight and underweight. Being overweight can affect the cholesterol level in the body, one of the most important factors for determining the risk in a person to suffer from degenerative diseases. Based on the result of the research survey, 46.2% elderly at Posyandu Blulukan are categorized as obese. Purpose : This study was aimed to determine the relationship of body mass index with the total cholesterol level of elderly at Posyandu Lansia. Research methods : This study was an observational study with cross sectional method. The samples were taken from the population based on the inclusion and exclusion criteria, and therefore obtained 36 respondents. The sampling technique was done by using consecutive sampling method. The body mass index was obtained from the measurements of weight and height. The total cholesterol level was obtained by using a spectrophotometer. The correlation test was done by using Pearson Product Moment. Results : Based on the univariate analysis, obtained the nutritional status of respondents, overall are having more nutrition (72.2%) and most of the total cholesterol level of the respondent are more than normal portion (44.6%). Based on Pearson Product Moment test, indicated the results of the analysis of body mass index with the total cholesterol level with pvalue = 0.857 (> 0.05), means that there is no relationship of body mass index with the total cholesterol level. Conclusion : There is no relationship between body mass index with the total cholesterol level of elderly at Posyandu Lansia "Ngudi Waras" Blulukan, Colomadu, Karanganyar, Central Java. Suggestions : For other researchers, prior to performing nutritional status should add the variable of food intake in the elderly to obtained valid data.